النظام القانوني للحملة الانتخابية في الدول المغاربية (الجزائر، تونس، المغرب) - بولعراس، يوسف (Universty of El-oued جامعة الوادي, 2024)
تعالج هذه الأطروحة موضوعا على درجة كبيرة جدا من الأهمية في إرساء مسار البناء المؤسساتي في الدولة، ويتعلق بدراسة مقارنة للنظام القانوني للحملة الانتخابية في الدول المغاربية وتحديدا في كل من الجزائر وتونس والمغرب، حيث تعد الحملة الانتخابية مرحلة مهمة من مراحل العملية الانتخابية، ونجاح هذه الأخيرة مرهون بمدى نجاح مرحلة الحملة والذي لا يتأتى إلا من خلال وضع ضمانات قانونية كفيلة بإجرائها وفقا لمبادئ العدالة والمساواة، بما يعزز الديمقراطية التشاركية، ويكفل حماية صوت الناخب من خلال تنظيم انتخابات نزيهة وشفافة. كما تناولت هذه الدراسة جملة القوانين الناظمة للحملة الانتخابية في الدول الثلاث، بدءا من المبادئ الأساسية التي ترتكز عليها الحملة الانتخابية، وكذلك مختلف أساليب إدارتها وتنظيمها، خاصة في حالة الظروف الاستثنائية التي عرفها العالم ممثلة في جائحة كورونا، أين يعتبر الحفاظ على انتظامية مختلف الاستحقاقات تحديا رفعته الجزائر على غرار تونس والمغرب، مع الإشارة إلى النقص الذي لازال يعتري القوانين المغاربية الناظمة للحملة الانتخابية الالكترونية، وعلى مختلف مواقع التواصل الاجتماعي. وضمانا من المشرع المغاربي، في تنظيم حملة انتخابية تحترم إرادة الناخبين، عمل على إصلاح وتحيين تشريعاته وقوانينه الانتخابية، بما يحقق جملة من الضوابط الرقابية الإدارية والقضائية والسياسية على الحملة، بدءا من بسط رقابة فعالة على حساباتها تمويلا وإنفاقا، وانتهاء برصد مختلف الجرائم الانتخابية التي يمكن أن تحدث طوال فترة الحملة، مع ترتيب الجزاءات القانونية المناسبة لها، والتي تختلف من دولة لأخرى وحسب درجة الجريمة ونوع الاستحقاق. This thesis deals with a very important topic in establishing the path of institutional building in the state, and it concerns a comparative study of the legal system of the electoral campaign in the Maghreb countries, specifically in Algeria, Tunisia and Morocco, where the electoral campaign is an important stage of the electoral process, and the success of the latter depends on the success of the campaign phase, which can only come through the development of legal guarantees to ensure its conduct in accordance with the principles of justice and equality, in order to strengthen participatory democracy, and ensure the protection of the voter's voice through the organization of fair and transparent elections. This study dealt with the set of laws governing the electoral campaign in the three countries, starting from the basic principles on which the electoral campaign is based, as well as various methods of its management and organization, especially in the case of exceptional circumstances that the world has known, represented by the corona pandemic, where maintaining the regularity of various benefits is a challenge raised by Algeria, similar to Tunisia and Morocco, with reference to the shortage of laws governing the electronic electoral campaign, and on various social networking sites. In order to ensure that the Maghreb legislature organizes an electoral campaign that respects the will of the voters, it has worked to reform and update its electoral legislation and laws, in order to achieve a set of administrative, judicial and political controls on the campaign, starting with effective control over its accounts, financing and spending, and ending with monitoring various electoral crimes that may occur throughout the campaign period, with the arrangement of appropriate legal sanctions, which vary from one country to another and according to the degree of crime and the type of entitlement.
- دراسة مقارنة -
أطروحة دكتوراه تخصص قانون الدولة والمؤسسات في الحقوق والعلوم السياسية
Keywords: الحملة الانتخابية – السلطة الوطنية المستقلة للانتخابات– الهيئة العليا المستقلة للانتخابات- لجنة مراقبة تمويل الحملة الانتخابية- محكمة المحاسبات- المجلس الأعلى للحسابات.; Electoral campaign - Independent National Election Authority - Independent High Electoral Commission - Election Campaign Financing Monitoring Committee - Court of Accounts - Supreme Council of Accounts